Perancangan Interior Fasilitas Bagi Komunitas Sepeda Tua di Surabaya - Afriansyah Winata; Lintu Tulistyantoro; yohan santoso (Intra, 2016)
Surabaya is one big city that has a lot of culture or what we call multicultural caused many hobbies in common, one of which collects old bikes. Indonesia old bike community is a community that collects a lot of old bicycles and to educate the public about the collection of old bicycle and how to take care of the bike and do not have the facilities to accommodate. A facility design with contrast concept is designed to accommodate every activity of this old bike community, ranging from collecting, gathering, educating to tamper with spare-parts that have been damaged. Contrasting design concept enthusiasts will attract visitors to stop by and see the collection of the gallery this community, with a design that contrasts well as visitors will not feel bored while and was looking through a collection of old bikes there. A café designed addition to facilitating routine gathering of old bike community, this café can also be visited by the public and visitors gallery.